2008
DOI: 10.1055/s-2007-995783
|View full text |Cite
|
Sign up to set email alerts
|

Small-bowel neoplasms in patients undergoing video capsule endoscopy: a multicenter European study

Abstract: Our data suggest that VCE detects small-bowel tumors in a small proportion of patients undergoing this examination, but the early use of this tool can shorten the diagnostic work-up and influence the subsequent management of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
171
4
7

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 218 publications
(186 citation statements)
references
References 40 publications
4
171
4
7
Order By: Relevance
“…The mean age of patients with small bowel tumors was 47.1 years, which was lessened by the patients with benign polyps such as Peutz-Jeghers polyps, and the mean age of patients with GISTs/leiomyomata, lymphomas, or adenocarcinomas was above 50 years. Although the mean age of the patients with small bowel tumors was above 60 years in several CE studies [4][5][6][7][8][9][10], the mean age of those patients with small bowel tumors was 53 years in a Japanese DBE study [17], which is comparable with our results. The disagreement is not thought to be because of racial difference but because of the difference of the mean age between patients who received CE and patients who underwent DBE.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The mean age of patients with small bowel tumors was 47.1 years, which was lessened by the patients with benign polyps such as Peutz-Jeghers polyps, and the mean age of patients with GISTs/leiomyomata, lymphomas, or adenocarcinomas was above 50 years. Although the mean age of the patients with small bowel tumors was above 60 years in several CE studies [4][5][6][7][8][9][10], the mean age of those patients with small bowel tumors was 53 years in a Japanese DBE study [17], which is comparable with our results. The disagreement is not thought to be because of racial difference but because of the difference of the mean age between patients who received CE and patients who underwent DBE.…”
Section: Discussionsupporting
confidence: 89%
“…In the past, the diagnosis of small bowel tumors was made mainly through SBFT, abdominal CT, or even laparotomy; however, more accurate diagnosis for small bowel tumors became possible after the development of CE and DBE. The frequency of small bowel tumors in patients who receive CE has been reported to be 1.6-8.9% [4][5][6][7][8][9][10], while the frequency in patients who receive DBE is 10.0, 11.5 and 13.9% according to studies performed in Germany, Portugal, and Japan, respectively [15][16][17]. This difference is because DBE is usually performed to confirm abnormal findings that have been detected by other imaging studies, including CE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This has led to an idea that CE doubled the rate of diagnosing SB tumors. However, a recent multicenter European study showed that the frequency of SB tumors was 2.4% and the most common indication for CE was OGIB Rondonotti et al, 2008). SB tumors appear as masses or polyps in most patients and ulcer or stenoses in a minority of patients.…”
Section: Small Bowel Tumors and Polypsmentioning
confidence: 99%